OBA in Infrastructure : The Experience So Far - World Bank (World Bank, Washington, DC, 2017)
Increasing access to basic infrastructure services is critical to reducing poverty and enabling poor and marginalized people to participate in and benefit from economic development. Too often, however, the gap between the cost of the initial service connection and a user’s ability to pay for that connection prevents the poor from availing of basic services. Output-based aid (OBA), a form of results-based financing (RBF), addresses this gap, supporting poor people in accessing services such as household connections to the water supply or electricity grid, renewable energy systems, or solid waste management. By promoting the inclusion of people who may otherwise be left out of development gains, as well as encouraging utility sector reform, OBA supports the goal of universal access to basic services, one of the aims of the Sustainable Development Goals. This paper highlights the BA experience in infrastructure so far and the results achieved.